1994
DOI: 10.1103/physreve.50.3601
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian wave-packet dynamics: Semiquantal and semiclassical phase-space formalism

Abstract: Gaussian wavepackets are a popular tool for semiclassical analyses of classically chaotic systems. We demonstrate that they are extremely powerful in the semiquantal analysis of such systems, too, where their dynamics can be recast in an extended potential formulation. We develop Gaussian semiquantal dynamics to provide a phase space formalism and construct a propagator with desirable qualities. We qualitatively evaluate the behaviour of these semiquantal equations, and show that they reproduce the quantal beh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
100
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 54 publications
0
100
0
Order By: Relevance
“…If one is interested in the local dynamics around a point (say, at the bottom or top of the potential well), the set of equations get decoupled and it is easy to obtain simple analytic solutions of (55a)-(55e) for x and δx 2 for (54a). The higher order estimates (e.g., fourth order) of the quantum corrections can be obtained from the solutions of the equations of successive higher order derived earlier by Sundaram and Milonni [43] or otherwise [44]. Since the quantum corrections due to the system are calculated by different sets of equations for succesive orders, the measure of accuracy of truncation can be understood easily.…”
Section: Quantum Smoluchowski Equationmentioning
confidence: 99%
“…If one is interested in the local dynamics around a point (say, at the bottom or top of the potential well), the set of equations get decoupled and it is easy to obtain simple analytic solutions of (55a)-(55e) for x and δx 2 for (54a). The higher order estimates (e.g., fourth order) of the quantum corrections can be obtained from the solutions of the equations of successive higher order derived earlier by Sundaram and Milonni [43] or otherwise [44]. Since the quantum corrections due to the system are calculated by different sets of equations for succesive orders, the measure of accuracy of truncation can be understood easily.…”
Section: Quantum Smoluchowski Equationmentioning
confidence: 99%
“…This is also in agreement with the study of Pattanyak and Schieve [3] who have shown that, for a double well potential, squeezed coherent states show the most complex behavior for energies close to the separatrix. They argue [9] that the interplay between the classically unstable orbits and the quantum tunneling effects is the origin of this complex behavior. This is in agreement with our observations on the behavior of the energy level statistics in that regime.…”
mentioning
confidence: 99%
“…However for a practical calculation we need a recipe for calculation of Q(t). This has been discussed earlier in several contexts 24,25,26,27,39,40 . For the present purpose we summarize it as follows:…”
Section: A Quantum Langevin Equation In C-numbersmentioning
confidence: 94%
“…In Appendix A we have derived the equations for quantum corrections upto forth oder 39 . Under very special circumstances, it has been possible to include quantum effects to all orders 27,40 . The present theory thus takes into account of the anharmonicity as an integral part of the treatment.…”
Section: A Quantum Langevin Equation In C-numbersmentioning
confidence: 99%